Policy Dynamics of the pink tide of regime change in Latin America - Henry Veltmeyer (Revista nuestrAmérica, 2021)
The purpose of this paper is to advance an argument that might explain the dynamics of recent political developments in Latin America. The argument is constructed as follows. First, I review the dynamics of what Raúl Zibechi (2012) has described as the new geoeconomics of capital in Latin America and the corresponding politics. The paper then elaborates on certain dynamics associated with the political economy of two types of capitalism, with reference here to the particular way in which these forms of capital are combined in the current context of capitalist development in the region. The third part of the paper provides a brief review of the economic and political dynamics that led to the pink tide of regime change in South America. Subsequently, we provide a brief review and analysis of the policy dynamics of the governments formed in the wake of this seatide of regime change and the associated progressive cycle in Latin American politics. The paper then turns towards the recent pendulum swing of electoral politics towards the hard right of neoliberal policy reform. The paper ends with a brief discussion of the forces that might be involved in what appears to be the end of the progressive cycle. The conclusion is that the answer can be found in various contradictions of extractive capitalism.